An Investigation into Valuation Inspection Templates amongst Estate Surveyors and Valuers in Nigeria - Onyejiaka, J. C.; Uzor, S. O.; Anyigor, C. K. (International Journal of Real Estate, 2025)
This study investigated valuation inspection templates amongst Estate Surveyors and Valuers in Nigeria. The research aims to determine the extent to which Estate Surveyors and Valuers use standard valuation inspection template and to identify the challenges associated. The study utilized a mixed-methods research design, combining both qualitative and quantitative approaches. A total of 260 Estate Surveyors and Valuers respondents were surveyed using a structured questionnaire. The  study  uncovered  the  level  of  adoption  Estate  Surveyors  and  Valuers  have  on  the  use  of standard valuation inspection template in Nigeria. They should follow international standard and local code of ethics. However, the study tried identifying whether there are adequate regulatory frameworks to ensure compliance with the set minimum standard. The research identified that due to  the  differing  nature  of  properties,  firms  produce  in-house  and  ad-hoc  template  to  forester practice flexibility, also the study strived to reveal any lacuna and discrepancies in this regard as it relates with the need for Estate Surveyors and Valuers to adopt global best practices  to forester credibility  of  the  process  and  improve  the  valuation  procedure  in  general  and  the  need  for improvement. The research recommends regulatory harmonization, and technology adoption to enhance capacity building and training of Estate Surveyors and Valuers in inspection in general.
Keywords: Valuation; Inspection Template; Estate Surveyors and Valuers; Checklist